2001
DOI: 10.1359/jbmr.2001.16.6.1130
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density and Bone Loss Measured at the Radius to Predict the Risk of Nonspinal Osteoporotic Fracture

Abstract: Low bone mineral density (BMD) and, probably, the rate of bone loss (RBL) are associated with the risk of osteoporotic fractures. To estimate the risk of nonspinal fracture in osteoporotic women, we measured BMD and RBL in a prospective study (average follow-up, 5.38 years) in 656 postmenopausal women. The women were considered in three groups: group A (whole population), group B (women under the age of 65years) and group C (women over the age of 65 years). At the beginning of the study, BMD was measured at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 29 publications
4
15
0
Order By: Relevance
“…Our results indicated that distal forearm bone loss is a predictor of incident non-vertebral fracture, independent of baseline BMD, in postmenopausal women and can be compared with data from other prospective studies [14][15][16][17][18][19], only one of them including men [19]. Riis et al reported that baseline forearm bone mass and rate of bone loss predisposed to the same extent to fractures [14], whereas, Gnudi et al reported that rate of bone loss at the proximal but not distal radius was significantly associated with fracture risk in women over the age of 65 years [15].…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Our results indicated that distal forearm bone loss is a predictor of incident non-vertebral fracture, independent of baseline BMD, in postmenopausal women and can be compared with data from other prospective studies [14][15][16][17][18][19], only one of them including men [19]. Riis et al reported that baseline forearm bone mass and rate of bone loss predisposed to the same extent to fractures [14], whereas, Gnudi et al reported that rate of bone loss at the proximal but not distal radius was significantly associated with fracture risk in women over the age of 65 years [15].…”
Section: Discussionsupporting
confidence: 51%
“…Riis et al reported that baseline forearm bone mass and rate of bone loss predisposed to the same extent to fractures [14], whereas, Gnudi et al reported that rate of bone loss at the proximal but not distal radius was significantly associated with fracture risk in women over the age of 65 years [15]. Nevertheless, in the OFELY study, women with incident fractures had 38-53% higher rates of bone loss prior to fracture compared with those without fracture, and bone loss in the highest tertiles at the distal, mid-, and ultra-distal radius was significantly associated with increased risk of all fractures [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 As the life expectancy is increasing even in the developing countries, by the year 2035 the maximum number of osteoporosis cases in the world will be in India and China. 10 The current study had shown that increasing age has negative correlation with T-score forearm. More number of osteoporotic subjects were in 56-60 years age group as compared to 46-50 years.…”
Section: Discussionmentioning
confidence: 48%
“…The rate of bone loss, which is variable among postmenopausal women, has been postulated to be an independent risk factor for fracture [4,5]. However, few prospective studies have assessed the association between the rate of bone loss and the risk of fracture [6][7][8][9][10]. In three of these studies however, the rate of bone loss was only obtained from the forearm site [6][7][8].…”
Section: Introductionmentioning
confidence: 99%